(Effects of Pre-treatments in Relation to Breaking Dormancy of Ketapang Kencana (Terminalia mantaly H. Perrier) Seeds - Arum Sekar Wulandari; Dela Meisuda Mar’Atussholihah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
The dormancy of Ketapang kencana seeds can be removed by using pre-treatment in order to breaking dormancy of seeds. The aim of this study was to analyze the effect of pre-treatment for breaking dormancy of seeds, and the seed size on the Ketapang kencana seed germination. Ketapang kencana seeds that have been extracted are classified into 3 sizes, such as: large, medium and small. After that, the seeds were treated with dormancy breaking, such as: (1) control, (2) seeds cutting, (3) seeds sanding, (4) seeds soaking in H2SO4 solution, (5) seeds soaking in hot water (temperature ± 80 oC) for 10 minutes, (6) seeds soaking in water for 12 hours, and (7) seeds soaking in water for 72 hours. The results showed that there were 3 pre-treatments of seeds dormancy breaking that could increase the seed germination, such as cutting the seeds on the endocarp, sanding the seeds on the endocarp, and soaking the seeds in the water for 12 hours. The pre-treatments of seeds dormancy breaking significantly affected the germination index, normal sprout growth (dry weight, height, root length), and the start of sprout growth. Ketapang kencana seed size affected the germination and the dry weight of normal sprouts. The large seeds (0.65–0.82 cm) had the highest germination and dry weight. In general, the pre-treatment of seeds dormancy breaking and the seed size increased the germination of Ketapang kencana seeds. Key words: maximum growth potential, seed germination, seed size, seed viability, seed vigour